2017
DOI: 10.3310/hta21170
|View full text |Cite
|
Sign up to set email alerts
|

PET-NECK: a multicentre randomised Phase III non-inferiority trial comparing a positron emission tomography–computerised tomography-guided watch-and-wait policy with planned neck dissection in the management of locally advanced (N2/N3) nodal metastases in patients with squamous cell head and neck cancer

Abstract: a multicentre randomised Phase III non-inferiority trial comparing a positron emission tomographycomputerised tomography-guided watch-and-wait policy with planned neck dissection in the management of locally advanced (N2/N3) nodal metastases in patients with squamous cell head and neck cancer. Health Technol Assess 2017;21(17). This journal is a member of and subscribes to the principles of the Committee on Publication Ethics (COPE) (www.publicationethics.org/). Health Technology Assessment is indexed and abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 71 publications
1
54
0
2
Order By: Relevance
“…Analysis of Trans Tasman Radiation Oncology Group Study 98.02 demonstrated a zero incidence of isolated neck failures in patients that had a complete clinical and radiographic response [ 18 ]. More recently, Mehanna et al demonstrated that post-CRT PET-CT-guided surveillance showed similar survival outcomes compared to planned neck dissection in those patients with N2 and N3 disease [ 19 ]. In our analysis, we found similar regional control rates in patients that underwent CRT alone with those that went on to receive planned neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of Trans Tasman Radiation Oncology Group Study 98.02 demonstrated a zero incidence of isolated neck failures in patients that had a complete clinical and radiographic response [ 18 ]. More recently, Mehanna et al demonstrated that post-CRT PET-CT-guided surveillance showed similar survival outcomes compared to planned neck dissection in those patients with N2 and N3 disease [ 19 ]. In our analysis, we found similar regional control rates in patients that underwent CRT alone with those that went on to receive planned neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…12 This approach, in patients treated nonsurgically with advanced neck disease, has been demonstrated to be more cost-effective with similar survival compared to a planned neck dissection in the posttreatment period. [43][44][45] 2 | CON CLU S IO N The incidence of CUP is increasing but with advances in immunohistochemical staining, imaging, and intraoperative visualization of high-risk subsites has increased the likelihood of identifying the primary site. The PET-CT scans are indicated for CUP before surgical endoscopy and biopsies.…”
Section: Follow-up and Surveillancementioning
confidence: 99%
“…In situations in which there is an inadequate response in the neck from a nonsurgical approach with persistence of a neck mass, a PET‐CT scan can be used with an excellent negative predictive value . This approach, in patients treated nonsurgically with advanced neck disease, has been demonstrated to be more cost‐effective with similar survival compared to a planned neck dissection in the posttreatment period …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, clear advantages of PET-CT were determined in a study regarding PET-CT follow-up compared to neck dissection. However, these results only apply to N2 stages and the authors emphasize that it does not seem possible to apply the results to the N3 stage [9,10]. In consideration of the increasingly differentiated approach to different receptor-and gene-associated tumor entities, a study regarding the detection of metastases in "breast cancer" no longer seems up-to-date, for example.…”
Section: Htas In Radiologymentioning
confidence: 99%
“…▶ Table 4 Overview of the number of HTA reports in radiology in the period 2012 -2017, source [23], pg. 594 publication year organ system imaging modality source 2017 breast Mammo, MRI [24] head/neck PET-CT [10] 2016 lung CT [25] lung CT, DCE-CT, FDG-PET-CT [26] all PET-CT, PET-MRI [27] 2015 breast CT [28] abdomen CTC [29] 2014 neuro MR-DWI, CT [30] all MRI [31] 2013 abdomen TE [32] abdomen Sono, CT, MRI [33] 2012 cardio CT-angio, angio [34] CTC -CT-colonography; TEtransient elastography; DCE-CTdynamic contrast-enhanced CT; FDG-PET-CT -18-fluorodeoxyglucose-positron emission tomography; MR-DWImagnetic resonance diffusion-weighted brain imaging; PETpositron emission tomography.…”
Section: Htas: Lack Of Demand Lack Of Supplymentioning
confidence: 99%